(3OQGSGJ aj fXQjI GdGJUGd (B:s (3fMh acQ EYdGej eJejR (B/s - (3YRjs ((3HjQhJ (B:s (3eQcR OQGSGJ GdhMOI GdYQHjI ,s, 2003)
....(3h MSHfG Gf fXQjI GJUGdjI MVGQjI HOjdI HGJJ JaQV faSgG fXQjG h YdejG h jaJQV WQMfG Gf GdGJUGd eQJHW HGJbfjGJ GdMOjKI ddGJUGd h HNGUI GdGJUGd GdeQFj jchf gGOaG h OGdG MVGQjG GPG ecf GdaQO ef JMbjb PGJg GdeJcGedI aj GHYGOgG GdeYfhjI h GdLSOjI h GdeLJeY ef JMbjb GdGgOGa GdQSGdjI h GdeYjTjI GdeQJHWI jKbGaJg h GUhdg h eUGdMg(B......s
(3HHdjhZQGajG (B: (3U(B.145-151s
Keywords: (3GHSJjehdhLjG GdGJUGds; (3GdEYdGes; (3JcfhdhLjG GdGJUGds; (3hSGFd GdGJUGds